The Effects of Proximal Fibular Osteotomy on the Knee and Ankle Joints: a Finite Element Analysis - Unal, O. K.; Dagtas, M. Z.; Demir, C.; Najafov, T.; Ugutmen, E. (GALEN SRO, 2021)
PURPOSE OF THE STUDY In this study, our aim is to examine the effect of proximal fibular osteotomy on knee and ankle kinematics with finite element analysis method. MATERIAL AND METHODS One 62-year-old, female volunteer's radiologic images were used for creating lower limb model. Osteotomized model (OM) which was created according to definition of PFO and non-osteotomized model (NOM) were created. To obtain a stress distribution comparison between the two models, 350 N of axial force was applied to the femoral heads of the models. RESULTS After PFO, the average contact pressure decreased 26.1% at the medial tibial cartilage and increased 42.4% at the lateral tibial cartilage. The Von Mises stresses decreased 57.1% at the femoral cartilage and decreased 79.1% at tibial cartilage. The stress on the tibial cartilage increased 44.6%, and stress on the talar cartilage increased 7.1% at the ankle joint. CONCLUSIONS FEA revealed that main loading at the knee joint shifted from medial tibial cartilage to the lateral tibial cartilage after PFO. Additionally, the stresses on each cartilage were redistributed across a wider and more peripheral area. FEA also demonstrated that the Von Mises stresses of the tibial and talar cartilages of the ankle joint increased after PFO.
Keywords: knee pain; osteoarthritis; osteotomy; finite element analysis; axial loadings; COLLATERAL LIGAMENTS; MODEL; Orthopedics